STUDI ALTERNATIF PENEMPATAN BANGUNAN INSTALASI PENGOLAHAN AIR (IPA) DI WADUK SERMO - , Taufik Hidayat ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sermo Reservoir is a source of raw water at Sermo Water Treatment Plant (WTP) managed by PDAM Tirta Binangun Regency of Kulon Progo. Water intake at WTP of Sermo is implemented by pumping system, because the Installation is located at elevation of +163,29 m, while normal water level of reservoir is at +136,6 m. Most of the water distributed by gravity from WTP, and some others pumped to the higher elevation area. Operating on the system requires many of pump usage, so the impact on energy cost is quite high. This study examines an alternative if WTP of Sermo located at an elevation that allows the intake of water from Sermo reservoir by gravity. The influence of the placement of the alternative WTP to the Network of SPAM Sermo examined in terms of network characteristics and its performance technically, electrical costs of pumps on the system, and financing of the network of SPAM Sermo in general. Simulation implemented by using software of waternet 2.2, on both of network condition, first is the network with existing WTP, which water intake implemented by pumping system, and the second is the network with an alternative positioned WTP, which water intake implemented by gravity. In each of those conditions, simulations performed at discharge scenario : 45 l/s (existing), 60 l/s, 90 l/s, 120 l/s and 150 l/s. Simulations conducted thus indicating that network performance indicators meet the water demand and pumps used have good efficiency. From the result of simulation can be known pump operating costs on both network conditions to be compared. Financial analysis implemented on investment on each of the simulation by the method of Benefit Cost Ratio (BCR) and Net Present Value (NPV) at 12% interest rate. The results of simulation show that network with the alternative WTP provide pump operating costs lower than network with the existing WTP. Percentage of savings increase as the increase of discharge that managed by the network, that is 27.03% per year on the 45 l/s of discharge scenario, up to 37.59% per year on the 150 l/s of discharge scenario. The network with Alternative WTP known more financially viable than the network with existing WTP, which the value of BCR and NPV of the network with alternative WTP is always larger than the network with existing WTP. In the 30th year (150 l/s of discharge scenario), BCR value of the network with alternative WTP is 1.84 while the network with existing IPA is 1.70. NPV value of the network with Alternative WTP is Rp. 83,721,594,245 while the network with existing WTP is Rp. 75,356,129,812.